Negative electrode additive as well as preparation method and application thereof
By preparing negative electrode additives with hollow structure, the problem of deterioration of infiltration caused by the decrease in porosity of the negative electrode sheet is solved, and the effect of improving the infiltration performance of the negative electrode sheet and the battery circulation capacity is achieved.
Patent Information
- Application Number
- CN202411529780.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-30
AI Technical Summary
After the negative electrode compaction is increased, the porosity of the negative electrode sheet decreases, resulting in poor infiltration and abnormal problems such as lithium-ion center of the electrode sheet.
By mixing polyvinyl alcohol, template agent, phosphate buffer and soluble calcium source, and adjusting the pH through alkali liquid, negative electrode additives with hollow structure, suitable particle size and wall thickness are prepared to improve the wetting performance of the negative electrode sheet.
The liquid absorption speed and wetting performance of the negative electrode are improved, the ratio of being crushed is reduced, the comprehensive electrochemical performance of the negative electrode sheet is improved, and the circulation capacity of the battery is improved under the 4C fast charging cycle standard.
Smart Images

Figure CN119419273A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a negative electrode additive and a preparation method and application thereof. Background Art
[0002] Batteries have the characteristics of high capacity and long life, and are widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric cars, electric airplanes, electric toy cars, and electric toy ships. As the energy density of batteries increases step by step, there are further requirements for the compaction of positive and negative electrodes. Among them, the negative electrode itself has good conductivity as graphite, making it possible to use liquid retaining agents with relatively high resistivity in the negative electrode. However, as the compaction of the negative electrode increases, the porosity of the negative electrode plate decreases significantly, resulting in poor wetting, and abnormal problems such as lithium precipitation in the center of the plate will occur.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] One object of the present invention is to provide a method for preparing a negative electrode additive. By combining various raw materials and steps, the obtained negative electrode additive has good liquid absorption performance and can improve the wetting performance of the negative electrode sheet.
[0005] Another object of the present invention is to provide a negative electrode additive having a hollow structure, suitable particle size and wall thickness, good physical and chemical properties, and capable of improving the wettability of the negative electrode.
[0006] Another object of the present invention is to provide a negative electrode material layer.
[0007] Another object of the present invention is to provide a negative electrode sheet.
[0008] Another object of the present invention is to provide a battery.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] A method for preparing a negative electrode additive comprises the following steps:
[0011] Polyvinyl alcohol, a template agent, a phosphate buffer and a soluble calcium source are mixed to obtain a first system; an alkali solution is used to adjust the pH of the first system, and then solid-liquid separation is performed, and solids are collected to obtain a negative electrode additive.
[0012] In some embodiments, the weight average molecular weight of the polyvinyl alcohol is 10,000 to 55,000.
[0013] In some embodiments, the template comprises phytic acid and / or sodium phytate.
[0014] In some embodiments, the concentration of the polyvinyl alcohol in the phosphate buffer is 4-20 g / L.
[0015] In some embodiments, the concentration of the template in the first system is 6.6-66 g / L.
[0016] In some embodiments, the molar ratio of the soluble calcium source to the phosphate buffer is 1:1, calculated as calcium element and phosphate radical, respectively.
[0017] In some embodiments, the phosphate buffer comprises sodium chloride, potassium chloride, disodium hydrogen phosphate, potassium dihydrogen phosphate and water; the dosage ratio of the sodium chloride, potassium chloride, disodium hydrogen phosphate, potassium dihydrogen phosphate and water is 80g:2g:14.4g:2.4g:1000mL.
[0018] In some embodiments, the rotation speed of the mixing process is 200 to 400 rpm, and the time of the mixing process is 40 to 70 minutes.
[0019] In some embodiments, an alkali solution is used to adjust the pH of the first system to 7-10.
[0020] A negative electrode additive is prepared by adopting the negative electrode additive preparation method.
[0021] In some embodiments, the negative electrode additive has a hollow structure; the particle size of the negative electrode additive is 200 to 400 nm, and the wall thickness is 10 to 30 nm.
[0022] A negative electrode material layer comprises a negative electrode active material, a conductive agent, a binder and a negative electrode additive. The negative electrode additive is prepared by the negative electrode additive preparation method.
[0023] In some embodiments, the mass ratio of the conductive agent to the negative electrode additive is (1-2): (1-2).
[0024] In some embodiments, in the negative electrode material layer, the mass content of the negative electrode active material is 94% to 97%, the mass content of the conductive agent is 0.25% to 0.5%, the mass content of the binder is 2.5% to 5%, and the mass content of the negative electrode additive is 0.25% to 0.5%.
[0025] In some embodiments, the negative electrode active material includes graphite.
[0026] In some embodiments, the conductive agent includes conductive carbon black.
[0027] In some embodiments, the binder includes sodium carboxymethyl cellulose and styrene-butadiene rubber, and the mass ratio of the sodium carboxymethyl cellulose to the styrene-butadiene rubber is (1-1.5):2.
[0028] In some embodiments, the negative electrode material layer is prepared by drying the negative electrode slurry, and the preparation method of the negative electrode slurry specifically includes: subjecting the sodium carboxymethyl cellulose glue, the conductive agent, and the negative electrode additive to a first mixing treatment, then adding the negative electrode active layer material and the first solvent to a second mixing treatment, then adding styrene-butadiene rubber to a third mixing treatment, and adding the second solvent to obtain the negative electrode slurry.
[0029] In some embodiments, assuming that the total mass of the sodium carboxymethyl cellulose, styrene butadiene rubber, negative electrode active material, conductive agent and negative electrode additive is R, the mass of the conductive agent accounts for 0.25% to 0.5% of the total mass R, the total mass of the sodium carboxymethyl cellulose and styrene butadiene rubber accounts for 1.5% to 4.5% of the total mass R, the mass ratio of the sodium carboxymethyl cellulose and styrene butadiene rubber is (1 to 1.5):2, the mass of the negative electrode additive accounts for 0.25% to 0.5% of the total mass R, and the mass of the negative electrode active material accounts for 94% to 97% of the total mass R.
[0030] In some embodiments, the viscosity of the negative electrode slurry is 3000-4000 cps.
[0031] In some embodiments, the rotation speed of the first mixing treatment is: 3000-4000 rpm for rotation and 20-100 rpm for revolution, and the time of the first mixing treatment is 1-2 hours.
[0032] In some embodiments, the rotation speed of the second mixing treatment is: 3000-4000 rpm for rotation and 20-100 rpm for revolution, and the time of the second mixing treatment is 3-4 hours.
[0033] In some embodiments, the rotation speed of the third mixing process is: 500-700 rpm for rotation and 20-50 rpm for revolution, and the time for the third mixing process is 20-35 min.
[0034] A negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer arranged on at least one side surface of the negative electrode current collector, wherein the negative electrode material layer is the negative electrode material layer described above.
[0035] A battery comprises the negative electrode sheet.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] (1) The preparation method of the negative electrode additive of the present invention, the addition of polyethanol can cross-link the template to form nano-scale micelles, reduce the particle size of the final hydroxyapatite nanoparticles, and through the coordination of various raw materials and steps, the obtained negative electrode additive has a hollow spherical structure, a particle size of 200 to 400 nm, a wall thickness of 10 to 30 nm, good liquid absorption performance, which can increase the liquid absorption speed of the negative electrode and improve the wetting performance of the negative electrode sheet.
[0038] (2) The negative electrode additives mentioned above are added to the negative electrode material layer of the present invention to replace part of the conductive agent and fill between the negative electrode active materials to reduce the rate of being crushed, thereby improving the wettability of the negative electrode material layer.
[0039] (3) The negative electrode sheet of the present invention has excellent wettability and good comprehensive electrochemical performance.
[0040] (4) The battery of the present invention has improved cycle capacity under the 4C fast charging cycle standard without causing degradation of other electrical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0042] Figure 1 This is a transmission electron microscope image of the negative electrode additive in Example 1 of the present invention. DETAILED DESCRIPTION
[0043] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0044] According to one aspect of the present invention, the present invention relates to a method for preparing a negative electrode additive, comprising the following steps:
[0045] Polyvinyl alcohol (PVA), a template agent, a phosphate buffer and a soluble calcium source are mixed to obtain a first system; an alkali solution is used to adjust the pH of the first system, and then solid-liquid separation is performed, and solids are collected to obtain a negative electrode additive.
[0046] The preparation method of the negative electrode additive of the present invention can cross-link the template agent to form nano-scale micelles by adding polyethanol, thereby reducing the particle size of the final hydroxyapatite nanoparticles. Through the coordination of various raw materials and steps, the obtained negative electrode additive has a hollow spherical structure and good liquid absorption performance, which can increase the liquid absorption speed of the negative electrode and improve the wetting performance of the negative electrode sheet.
[0047] In some embodiments, the weight average molecular weight of the polyvinyl alcohol is 10000 to 55000, such as 10000, 12000, 15000, 20000, 25000, 30000, 35000, 40000, 45000, 50000 or 55000, or any range between the two. The present invention uses polyvinyl alcohol with a suitable weight average molecular weight, which is more conducive to synergizing with the template agent to ensure the structural characteristics and physical and chemical properties of the final negative electrode additive.
[0048] In some embodiments, the template comprises phytic acid and / or sodium phytate. The concentration of the template in the first system is 6.6-66 g / L, such as 6.6 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 50 g / L, 66 g / L, etc.
[0049] In some embodiments, the concentration of polyvinyl alcohol in phosphate buffer is 4-20 g / L, for example, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 10 g / L, 12 g / L, 15 g / L, 18 g / L, 20 g / L, etc.
[0050] In some embodiments, the molar ratio of the soluble calcium source to the phosphate buffer is (1-2): (1-2) in terms of calcium element and phosphate radical, respectively.
[0051] In some embodiments, the phosphate buffer comprises sodium chloride, potassium chloride, disodium hydrogen phosphate, potassium dihydrogen phosphate and water; the dosage ratio of the sodium chloride, potassium chloride, disodium hydrogen phosphate, potassium dihydrogen phosphate and water is 80g:2g:14.4g:2.4g:1000mL. The preparation method of the phosphate buffer of the present invention is as follows: 80g sodium chloride, 2g potassium chloride, 14.4g disodium hydrogen phosphate and 2.4g potassium dihydrogen phosphate are dissolved in 800mL water, shaken until completely dissolved, and then fixed to 1000mL to obtain the required phosphate buffer.
[0052] In some embodiments, the rotation speed of the mixing treatment is 200-400 rpm, for example, 200 rpm, 250 rpm, 280 rpm, 300 rpm, 330 rpm, 350 rpm, 400 rpm, etc., and the time of the mixing treatment is 40-70 min, for example, 40 min, 50 min, 60 min, 70 min, etc.
[0053] In some embodiments, an alkali solution is used to adjust the pH of the first system to 7 to 10. The alkali solution includes a sodium hydroxide solution.
[0054] According to another aspect of the present invention, the present invention also relates to a negative electrode additive, which is prepared by the preparation method of the above-mentioned negative electrode additive. The negative electrode additive of the present invention has excellent physical and chemical properties and can improve the wetting performance of the negative electrode sheet. The negative electrode additive has a hollow structure; the particle size of the negative electrode additive is 200-400nm, such as 200nm, 220nm, 250nm, 280nm, 300nm, 320nm, 350nm, 380nm, 400nm, etc., and the wall thickness is 10-30nm, such as 10nm, 12nm, 15nm, 20nm, 22nm, 25nm or 30nm, etc.
[0055] In some embodiments, the particle size of the negative electrode additive is tested by a laser particle size analyzer to see the D50 value. The wall thickness is tested by a transmission electron microscope, taking photos to measure the wall thickness of more than ten particles and calculating the average value.
[0056] If a simple phytic acid template is used (without adding polyvinyl alcohol), hydroxyapatite hollow spheres with a diameter of 3 to 5 nm and a wall thickness of 50-100 nm will be formed. The structure of large-sized hollow particles is easily destroyed during the subsequent rolling process of preparing the negative electrode sheet, thereby affecting the electrochemical performance of the negative electrode sheet.
[0057] According to another aspect of the present invention, the present invention also relates to a negative electrode material layer, comprising a negative electrode active material, a conductive agent, a binder, and a negative electrode additive, wherein the negative electrode additive is prepared by the above-mentioned method for preparing the negative electrode additive.
[0058] The negative electrode additives added to the negative electrode material layer of the present invention can replace part of the conductive agent and can be filled between the negative electrode active materials to reduce the crushing ratio, thereby improving the wettability of the negative electrode sheet and ensuring the comprehensive electrochemical energy of the negative electrode sheet.
[0059] In some embodiments, the mass ratio of the conductive agent to the negative electrode additive is 1: 1. The conductive agent and the negative electrode additive of the present invention adopt a suitable mass ratio, thereby ensuring coordinated work to increase the liquid absorption rate of the negative electrode sheet without causing other performance degradation of the battery.
[0060] In some embodiments, in the negative electrode material layer, the mass content of the negative electrode active material is 94% to 97%, such as 94%, 95%, 96% or 97%, etc.; the mass content of the conductive agent is 0.25% to 0.5%, such as 0.25%, 0.3%, 0.4%, 0.45% or 0.5%, etc.; the mass content of the binder is 2.5% to 5%, such as 2.%, 3%, 3.5%, 4%, 4.5% or 5%, etc.; the mass content of the negative electrode additive is 0.25% to 0.5%, such as 0.25%, 0.3%, 0.4%, 0.45% or 0.5%, etc. In the negative electrode material layer of the present invention, the negative electrode additive is matched with other components in a suitable ratio, which is more conducive to improving the wetting performance of the negative electrode sheet and ensuring its comprehensive performance.
[0061] In some embodiments, the negative electrode active material includes graphite, and the graphite includes 4C graphite and / or 1C graphite.
[0062] In some embodiments, the conductive agent includes conductive carbon black;
[0063] In some embodiments, the binder includes sodium carboxymethyl cellulose and styrene-butadiene rubber, and the mass ratio of the sodium carboxymethyl cellulose to styrene-butadiene rubber is (1-1.5):2, such as 1:2, 1.1:2, 1:1.3, 1:1.4 or 1:1.5.
[0064] In some embodiments, the negative electrode material layer is prepared by drying the negative electrode slurry, and the preparation method of the negative electrode slurry specifically includes: subjecting sodium carboxymethyl cellulose glue, the conductive agent, and the negative electrode additive to a first mixing treatment, then adding the negative electrode active layer material and the first solvent to a second mixing treatment, then adding styrene-butadiene rubber to a third mixing treatment, and adding the second solvent to obtain the negative electrode slurry. The preparation method of the negative electrode material layer of the present invention is more conducive to ensuring the performance of the negative electrode slurry through the coordination of each step, which is conducive to improving the coating effect of the negative electrode sheet and improving the comprehensive performance of the film layer.
[0065] In some embodiments, assuming that the total mass of the sodium carboxymethyl cellulose, styrene butadiene rubber, negative electrode active material, conductive agent and negative electrode additive is R, the mass of the conductive agent accounts for 0.25% to 0.5% of the total mass R, the total mass of the sodium carboxymethyl cellulose and styrene butadiene rubber accounts for 1.5% to 4.5% of the total mass R, the mass ratio of the sodium carboxymethyl cellulose and styrene butadiene rubber is (1 to 1.5):2, the mass of the negative electrode additive accounts for 0.25% to 0.5% of the total mass R, and the mass of the negative electrode active material accounts for 94% to 97% of the total mass R.
[0066] In some embodiments, the concentration of sodium carboxymethylcellulose glue is 1.1% to 1.3%. The concentration of sodium carboxymethylcellulose glue in each example is 1.2%.
[0067] In some embodiments, the first solvent includes water. The first solvent accounts for 15% to 25% of the total mass of the slurry, for example 20%.
[0068] In some embodiments, the second solvent includes water. By adding the second solvent, the negative electrode slurry is adjusted to a desired viscosity.
[0069] In some embodiments, the viscosity of the negative electrode slurry is 3000-4000 cps, for example, 3000 cps, 3200 cps, 3500 cps, 3700 cps, 3800 cps, 3900 cps, 4000 cps, etc.
[0070] In some embodiments, the rotation speed of the first mixing treatment is: 3000-4000rpm (e.g., 3000rpm, 3400rpm, 3500rpm, 3800rpm, etc.), orbital speed is 20-100rpm (e.g., 20rpm, 30rpm, 50rpm, 80rpm or 100rpm), and the time of the first mixing treatment is 1-2h (e.g., 1h, 1.5h or 2h, etc.).
[0071] In some embodiments, the rotation speed of the second mixing treatment is: 3000-4000rpm (e.g., 3000rpm, 3500rpm, 4000rpm, etc.) on its own, 20-100rpm (e.g., 20rpm, 50rpm, 100rpm, etc.) on its orbit, and the time of the second mixing treatment is 3-4h (e.g., 3h, 3.5h or 4h, etc.).
[0072] In some embodiments, the rotation speed of the third mixing treatment is: 500-700 rpm (e.g., 500 rpm, 550 rpm, 600 rpm, etc.) for rotation, 20-50 rpm (e.g., 20 rpm, 30 rpm, 50 rpm, etc.) for revolution, and the time of the third mixing treatment is 20-35 min (e.g., 20 min, 25 min, 30 min or 35 min, etc.).
[0073] The present invention adopts appropriate first mixing condition, second mixing condition and third mixing condition to ensure that all materials are fully mixed and the performance of the slurry is guaranteed.
[0074] According to another aspect of the present invention, the present invention also relates to a negative electrode sheet, comprising a negative electrode current collector and a negative electrode material layer arranged on at least one side surface of the negative electrode current collector, wherein the negative electrode material layer is the negative electrode material layer described in the claims.
[0075] The negative electrode sheet of the present invention has excellent wettability and good comprehensive electrochemical performance.
[0076] According to another aspect of the present invention, the present invention also relates to a battery comprising the above-mentioned negative electrode sheet.
[0077] The battery of the present invention has improved cycle capacity under the 4C fast charge cycle standard without causing degradation of other electrical properties. In some embodiments, the battery includes the above-mentioned negative electrode sheet, positive electrode sheet, separator and electrolyte.
[0078] The following is further explained in conjunction with specific embodiments and comparative examples.
[0079] Example 1
[0080] A method for preparing a negative electrode additive comprises the following steps:
[0081] (1) 8 g / L of PVA (MW=10000) was dissolved in phosphate buffer, stirred at 300 rpm for 0.5 h, and sodium phytate was added to make the concentration of sodium phytate in the solution 66 g / L, stirred at 300 rpm for 0.5 h, and calcium chloride was added in an amount equimolar to the phosphate in the phosphate buffer to obtain the first system.
[0082] (2) The first system was neutralized with 0.5% mol / L NaOH and adjusted to pH = 7.
[0083] (3) Filter and separate the precipitate, and wash it three times with water to obtain a negative electrode additive.
[0084] The transmission electron microscope image of the negative electrode additive in this embodiment is as follows Figure 1 shown.
[0085] The method for preparing a negative electrode sheet comprises the following steps:
[0086] Carboxymethylcellulose sodium glue, conductive agent, and negative electrode additive are subjected to a first mixing treatment, wherein the speed of the first mixing treatment is 3800 rpm and the time of the first mixing treatment is 1.5 hours; then the negative electrode active layer material and the first solvent are added for a second mixing treatment, wherein the speed of the second mixing treatment is 3200 rpm and the time of the second mixing treatment is 3.5 hours; then styrene-butadiene rubber is added for a third mixing treatment, wherein the speed of the third mixing treatment is 600 rpm and the time of the third mixing treatment is 30 minutes; the second solvent is added to adjust the viscosity of the slurry to 3500 cps, and a negative electrode slurry is obtained. Among them, the mass of the negative electrode active material accounts for 96% of the total mass R of the binder (carboxymethylcellulose sodium and styrene-butadiene rubber), the negative electrode active material, the conductive agent, and the negative electrode additive, the mass of the conductive agent accounts for 0.35% of the total mass R, the mass content of the negative electrode additive is 0.35%, the mass of the carboxymethyl cellulose accounts for 1.3% of the total mass R, and the mass of the styrene-butadiene rubber accounts for 2% of the total mass R; the negative electrode active material is 4C graphite, the conductive agent is conductive carbon black, and the first solvent and the second solvent are deionized water.
[0087] The negative electrode slurry was coated on both sides of the copper foil and dried at 65° C. for 2 min to obtain a negative electrode sheet.
[0088] Example 2
[0089] A method for preparing a negative electrode additive, which differs from Example 1 in that:
[0090] The molecular weight of PVA is 50,000.
[0091] The preparation method of the negative electrode sheet is the same as that of Example 1 except that the negative electrode additive in this example is used.
[0092] Example 3
[0093] The method for preparing the negative electrode sheet is different from that of Example 1 in that:
[0094] The molecular weight of PVA is 30,000.
[0095] The preparation method of the negative electrode sheet is the same as that of Example 1 except that the negative electrode additive in this example is used.
[0096] Example 4
[0097] A method for preparing a negative electrode sheet, which differs from Example 2 in that:
[0098] The negative electrode active material is 1C graphite.
[0099] Example 5
[0100] A method for preparing a negative electrode additive comprises the following steps:
[0101] (1) 8 g / L of PVA (MW=20000) was dissolved in a phosphate buffer solution, stirred at 250 rpm for 35 min, and sodium phytate was added to make the concentration of sodium phytate in the solution 66 gmol / L; stirred at 250 rpm for 35 min, and calcium chloride was added in an amount equimolar to the phosphate in the phosphate buffer solution to obtain a first system.
[0102] (2) The first system was neutralized with 0.5% mol / L NaOH and adjusted to pH = 7.
[0103] (3) Filter and separate the precipitate, and wash it three times with water to obtain a negative electrode additive.
[0104] The method for preparing a negative electrode sheet comprises the following steps:
[0105] Carboxymethylcellulose sodium glue, conductive agent, and negative electrode additive are subjected to a first mixing treatment, wherein the speed of the first mixing treatment is 4000 rpm and the time of the first mixing treatment is 2 hours; then the negative electrode active layer material and the first solvent are added for a second mixing treatment, wherein the speed of the second mixing treatment is 3500 rpm and the time of the second mixing treatment is 3 hours; then styrene-butadiene rubber is added for a third mixing treatment, wherein the speed of the third mixing treatment is 500 rpm and the time of the third mixing treatment is 20 minutes; the second solvent is added to adjust the viscosity of the slurry to 3800 cps, and a negative electrode slurry is obtained. Among them, the mass of the negative electrode active material accounts for 96% of the total mass R of the binder (carboxymethylcellulose sodium and styrene-butadiene rubber), the negative electrode active material, the conductive agent, and the negative electrode additive, the mass of the conductive agent accounts for 0.5% of the total mass R, the mass content of the negative electrode additive is 0.5%, the mass of the carboxymethyl cellulose accounts for 1% of the total mass R, and the mass of the styrene-butadiene rubber accounts for 2% of the total mass R; the negative electrode active material is 4C graphite, the conductive agent is conductive carbon black, and the first solvent and the second solvent are deionized water.
[0106] The negative electrode slurry was coated on both sides of the copper foil and dried at 50° C. for 2 min to obtain a negative electrode sheet.
[0107] Example 6
[0108] A method for preparing a negative electrode additive comprises the following steps:
[0109] (1) Dissolve 16 g / L of PVA (MW=20,000) in phosphate buffer, stir at 350 rpm for 20 min, add sodium phytate so that the concentration of sodium phytate in the solution is 33 g / L, stir at 350 rpm for 20 min, add calcium chloride in an amount equimolar to the phosphate in the phosphate buffer, and obtain the first system.
[0110] (2) The first system was neutralized with 0.5% mol / L NaOH and adjusted to pH = 7.
[0111] (3) Filter and separate the precipitate, and wash it three times with water to obtain a negative electrode additive.
[0112] The method for preparing a negative electrode sheet comprises the following steps:
[0113] Carboxymethylcellulose sodium glue, conductive agent, and negative electrode additive are subjected to a first mixing treatment, wherein the speed of the first mixing treatment is 3600 rpm and the time of the first mixing treatment is 3 hours; then the negative electrode active layer material and the first solvent are added for a second mixing treatment, wherein the speed of the second mixing treatment is 3000 rpm and the time of the second mixing treatment is 4 hours; then styrene-butadiene rubber is added for a third mixing treatment, wherein the speed of the third mixing treatment is 700 rpm and the time of the third mixing treatment is 35 minutes; the second solvent is added to adjust the viscosity of the slurry to 3200 cps, and a negative electrode slurry is obtained. Among them, the mass of the negative electrode active material accounts for 95.5% of the total mass R of the binder (carboxymethylcellulose sodium and styrene-butadiene rubber), the negative electrode active material, the conductive agent and the negative electrode additive, the mass of the conductive agent accounts for 0.5% of the total mass R, the mass content of the negative electrode additive is 0.5%, the mass of the carboxymethyl cellulose accounts for 1.5% of the total mass R, and the mass of the styrene-butadiene rubber accounts for 2% of the total mass R; the negative electrode active material is 4C graphite, the conductive agent is conductive carbon black, and the first solvent and the second solvent are deionized water.
[0114] The negative electrode slurry was coated on both sides of the copper foil and dried at 80° C. for 2 min to obtain a negative electrode sheet.
[0115] Comparative Example 1
[0116] The method for preparing the negative electrode sheet is different from that of Example 1 in that:
[0117] No negative electrode additives were added during the preparation process, and the mass of the conductive agent accounted for 0.7% of the total mass R.
[0118] Experimental example
[0119] The negative electrode sheets in each embodiment and comparative example are respectively prepared into batteries, and the specific method includes:
[0120] Preparation of positive electrode sheet: Add PVDF and NMP to a double planetary mixer, mix at medium speed, disperse for 3 hours to obtain PVDF glue, add PVDF glue and SP to a double planetary mixer, disperse at medium speed for 1-2 hours, add NCM811 twice, add NMP, disperse at high speed for 2 hours each time, add appropriate amount of NMP after the end, and adjust the slurry viscosity to 3500cps. Apply on both sides of the aluminum foil by transfer coating, and bake in an oven at a temperature of 100°C for 2 minutes to obtain a positive electrode sheet. Assemble the above positive electrode sheet, negative electrode sheet, diaphragm and electrolyte to obtain a battery.
[0121] The wetting performance test was performed on the negative electrode sheets of each embodiment and comparative example. The test conditions included: at 25° C., dropping the electrolyte on the negative electrode sheet, and recording the time required for the electrolyte to be completely absorbed.
[0122] The resistivity test was performed on the negative electrode sheets of each embodiment and comparative example. The resistivity test method was to use a Kelley four-wire plus a controllable upper and lower plane double probe to form a series circuit for testing, place the electrode disc on the sample support jig of the electrode resistance meter, and test after closing the hatch.
[0123] The electrochemical performance test was performed on the batteries of various embodiments and comparative examples.
[0124] The test results are shown in Table 1.
[0125] Table 1 Test results
[0126]
[0127] It can be seen from Table 1 that the negative electrode additive obtained by the method of the present invention has excellent liquid absorption performance, and the negative electrode sheet prepared by replacing part of the conductive agent has excellent wetting performance.
[0128] In Examples 1 and 2, after the negative electrode additive replaced carbon black in equal amounts, except for a slight increase in the resistivity of the negative electrode sheet, all electrical properties did not deteriorate, with an improvement of 0.4% to 0.7% in 4C room temperature cycling for 600 cls, and an improvement of 0.8% to 1.2% in 4C, 45°C cycling for 600 cls.
[0129] Example 3 uses PVA with different molecular weights to obtain a negative electrode additive product whose short-term performance is basically consistent with that of Examples 1 and 2. Among them, Example 3 has a slight improvement of ~0.3% at 25°C and 4C rate cycle for 600cls, and an improvement of ~0.4% at 45°C and 4C rate cycle for 600cls.
[0130] In Examples 5 to 6, different ratios of PVA and phytic acid were used in comparison with Example 2, and the short-term performance and 4C rate cycle of the negative electrode additive products obtained were basically the same as those of Example 2.
[0131] After the negative electrode additive was used to replace the carbon black in equal amounts in Example 4, except for a slight increase in the resistivity of the negative electrode sheet, all electrical properties did not deteriorate. The cycle performance at room temperature and 45°C was slightly improved by 0.2% to 0.4%.
[0132] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a negative electrode additive, characterized in that: The following steps are involved: Polyvinyl alcohol, a template agent, a phosphate buffer and a soluble calcium source are mixed to obtain a first system; an alkali solution is used to adjust the pH of the first system, and then solid-liquid separation is performed, and solids are collected to obtain a negative electrode additive.
2. The method for preparing the negative electrode additive according to claim 1, characterized in that: Contains at least one of the following features (1) to (8): (1) The weight average molecular weight of the polyvinyl alcohol is 10,000 to 55,000; (2) The template comprises phytic acid and / or sodium phytate; (3) The concentration of the polyvinyl alcohol in the phosphate buffer is 4 to 20 g / L; (4) The concentration of the template in the first system is 6.6 to 66 g / L; (5) the molar ratio of the soluble calcium source to the phosphate buffer in terms of calcium element and phosphate radical is 1:1; (6) The phosphate buffer comprises sodium chloride, potassium chloride, disodium hydrogen phosphate, potassium dihydrogen phosphate and water; the dosage ratio of the sodium chloride, potassium chloride, disodium hydrogen phosphate, potassium dihydrogen phosphate and water is 80g:2g:14.4g:2.4g:1000mL; (7) The rotation speed of the mixing process is 200 to 400 rpm, and the time of the mixing process is 40 to 70 minutes; (8) Using alkaline solution to adjust the pH of the first system to 7-10.
3. A negative electrode additive, characterized in that: The negative electrode additive is prepared by the preparation method of the negative electrode additive according to claim 1 or 2.
4. The negative electrode additive according to claim 3, characterized in that: The negative electrode additive has a hollow structure; the particle size of the negative electrode additive is 200-400 nm, and the wall thickness is 10-30 nm.
5. A negative electrode material layer, characterized in that: The invention comprises a negative electrode active material, a conductive agent, a binder and a negative electrode additive, wherein the negative electrode additive is prepared by the preparation method of the negative electrode additive according to claim 1 or 2.
6. The negative electrode material layer according to claim 5, characterized in that: Contains at least one of the following features (1) to (5): (1) The mass ratio of the conductive agent to the negative electrode additive is (1-2): (1-2); (2) In the negative electrode material layer, the mass content of the negative electrode active material is 94% to 97%, the mass content of the conductive agent is 0.25% to 0.5%, the mass content of the binder is 2.5% to 5%, and the mass content of the negative electrode additive is 0.25% to 0.5%; (3) The negative electrode active material includes graphite; (4) The conductive agent includes conductive carbon black; (5) The binder comprises sodium carboxymethyl cellulose and styrene-butadiene rubber, and the mass ratio of the sodium carboxymethyl cellulose to the styrene-butadiene rubber is (1-1.5):
2.
7. The negative electrode material layer according to claim 5, characterized in that: The negative electrode material layer is prepared by drying the negative electrode slurry. The preparation method of the negative electrode slurry specifically includes: subjecting the sodium carboxymethyl cellulose glue, the conductive agent, and the negative electrode additive to a first mixing treatment, then adding the negative electrode active layer material and a first solvent to a second mixing treatment, then adding styrene-butadiene rubber to a third mixing treatment, and adding a second solvent to obtain the negative electrode slurry.
8. The negative electrode material layer according to claim 7, characterized in that: Contains at least one of the following features (1) to (5): (1) Assuming that the total mass of the sodium carboxymethyl cellulose, styrene butadiene rubber, negative electrode active material, conductive agent and negative electrode additive is R, the mass of the conductive agent accounts for 0.25% to 0.5% of the total mass R, the total mass of the sodium carboxymethyl cellulose and styrene butadiene rubber accounts for 1.5% to 4.5% of the total mass R, the mass ratio of the sodium carboxymethyl cellulose to styrene butadiene rubber is (1 to 1.5):2, the mass of the negative electrode additive accounts for 0.25% to 0.5% of the total mass R, and the mass of the negative electrode active material accounts for 94% to 97% of the total mass R; (2) The viscosity of the negative electrode slurry is 3000-4000 cps; (3) The rotation speed of the first mixing treatment is: 3000-4000 rpm, 20-100 rpm, and the time of the first mixing treatment is 1-2 hours; (4) The rotation speed of the second mixing treatment is: 3000-4000 rpm, 20-100 rpm, and the time of the second mixing treatment is 3-4 hours; (5) The rotation speed of the third mixing process is: 500-700 rpm for rotation and 20-50 rpm for revolution. The time of the third mixing process is 20-35 min.
9. A negative electrode sheet, characterized in that: The invention comprises a negative electrode current collector and a negative electrode material layer arranged on at least one side surface of the negative electrode current collector, wherein the negative electrode material layer is the negative electrode material layer according to any one of claims 5 to 8.
10. A battery, characterized in that: A negative electrode sheet comprising the negative electrode sheet according to claim 9.
Citation Information
Patent Citations
Additive for lithium ion battery as well as preparation method and application of additive
CN115395016A
Synthesis method of cobalt-doped hydroxyapatite microspheres
CN115557480A
Negative electrode slurry and preparation method thereof, negative electrode pole piece, battery and electric equipment
CN117080445A
Complex-phase calcium phosphate as well as preparation method and application thereof
CN117228644A
Electrochemical device and electronic device
CN117378054A